Relationship between Personality Characteristics and Sleep Quality, Daily Sleepiness and Quality of Life in University Students - Saeideh Baharloo; Mahmood Moosazadeh; Javad Setareh (Journal of Mazandaran University of Medical Sciences, 2021)
Background and purpose: Poor quality of sleep and excessive daytime sleepinessare major factors that impair health and quality of life. Theoretically, personality factors provide the biological and behavioral context that can affect sleep patterns and quality of life. The aim of this study was to present the status of sleep quality, excessive daytime sleepinessand quality of life in university students and also to determine the relationship between these factors and personality factors. Materials and methods: In this cross-sectional study, the students in Mazandaran University of Medical Sciences were selected by convenience sampling. Data were collected using a demographic questionnaire and Epworth Sleepiness Scale, Pittsburgh Sleep Quality Index, SF-12 quality of life, and NEO Five-Factor Inventory. Data analysis was performed in SPSS V24. Results: A total of 403 students (mean age= 22.83 ± 2.81 years), including 70.97% females participated in the study. Among the participants, 120 (29.77%) reported excessive daytime sleepiness, 64.52% had poor sleep quality, and 56.33% had poor or average quality of life. Good quality of life and good quality of sleep were found to be significantly associated with extraversion, agreeableness, and conscientiousness (P<0.05). There was a significant relationship between neuroticism and poor sleep quality and poor quality of life (P<0.05). Increase in age, decreased quality of life, and extraversion were observed to be associated with probability of decreased sleep quality (P<0.05). Conscientiousness and neuroticism were associated with excessive daytime sleepiness (P<0.05). Conclusion: Daytime sleepiness and poor sleep quality are both linked to neuroticism. Screening for sleep problems in students is necessary due to the relationship between personality traits and sleep quality that influence the quality of life.